2011
DOI: 10.1074/jbc.m111.239434
|View full text |Cite
|
Sign up to set email alerts
|

ATP and Mg2+ Promote the Reversible Oligomerization and Aggregation of Chloroplast 2-Cys Peroxiredoxin

Abstract: 2-Cys peroxiredoxins (2-Cys Prxs) are ubiquitous peroxidases with important roles in cellular antioxidant defense and hydrogen peroxide-mediated signaling. Post-translational modifications of conserved cysteines cause the transition from low to high molecular weight oligomers, triggering the functional change from peroxidase to molecular chaperone. However, it remains unclear how non-covalent interactions of 2-Cys Prx with metabolites modulate the quaternary structure. Here, we disclose that ATP and Mg 2؉(ATP/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The S P O 2 H of such sensitive Prxs can in many organisms be reactivated (Step 5) by ATP-dependent reduction by sulfiredoxin (Srx) or, perhaps, the less-characterized sestrin (46,113). How these Prxs facilitate peroxide signaling is not yet well understood but may involve a floodgate-like mechanism (265) and/or the formation of larger aggregates with molecular chaperone or other activities (12,89,197). Prx1 activity has also been reported to be regulated by phosphorylation (264).…”
Section: Catalytic Properties Of Prxsmentioning
confidence: 98%
“…The S P O 2 H of such sensitive Prxs can in many organisms be reactivated (Step 5) by ATP-dependent reduction by sulfiredoxin (Srx) or, perhaps, the less-characterized sestrin (46,113). How these Prxs facilitate peroxide signaling is not yet well understood but may involve a floodgate-like mechanism (265) and/or the formation of larger aggregates with molecular chaperone or other activities (12,89,197). Prx1 activity has also been reported to be regulated by phosphorylation (264).…”
Section: Catalytic Properties Of Prxsmentioning
confidence: 98%
“…Our previous studies revealed that ATP interacts with Cys R , , but nucleotide binding motives in 2-Cys Prx were not identified in an exhaustive search of protein databases. Therefore, we used QUANTUM version 3.3 that screens the interactions of proteins with drugs and metabolites to explore docking of ATP to different regions of 2-Cys Prx (Protein Data Bank entry ).…”
mentioning
confidence: 98%
“…Recently, circular dichroism (CD) spectroscopy revealed that changes in the secondary structure of 2-Cys Prx accompany the self-polymerization mediated by ATP/Mg. Again, if the C-terminal region is critical for the binding of ATP to His 6 -tagged 2-Cys Prx, the length of this extension should condition the response of the secondary structure to the binding of the nucleotide.…”
mentioning
confidence: 99%
See 2 more Smart Citations